Media self-regulation in the Pacific Islands: A survey of media professionals. Issue 1 (February 2016) - Weber, Ian; Johnson, James
Common concerns exist across the Pacific Islands' region over the quality of media reporting, absence of common media standards and enforcement mechanisms with regard to journalism ethics and implementation of increasingly tighter government regulations. This study surveyed working media professionals in the Pacific Islands on the feasibility of establishing a regional self-regulatory media system. It uses an internationally accepted analytical best practice framework and evaluative criteria for establishing media self-regulatory systems. A total of eight key findings, five recommendations and three implications for establishing a regional self-regulatory media system, were derived from the analysis of the survey data.